2020
DOI: 10.1027/1618-3169/a000474
|View full text |Cite
|
Sign up to set email alerts
|

Why People With High Alexithymia Make More Utilitarian Judgments

Abstract: Abstract. Although recent studies have investigated the effect of alexithymia on moral judgments, such an effect remains elusive. Furthermore, moral judgments have been conflated with the moral inclinations underlying those judgments in previous studies. Using a process dissociation approach to independently quantify the strength of utilitarian and deontological inclinations, the present study investigated the effect of alexithymia on moral judgments. We found that deontological inclinations were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Consistent with past research (e.g., Zhang et al, 2020 ), we did observe that childhood emotional abuse was positively associated with depression in the current study. The results from a recent study by Karaca Dinç et al (2021) suggest that both alexithymia and SPS may mediate this link.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with past research (e.g., Zhang et al, 2020 ), we did observe that childhood emotional abuse was positively associated with depression in the current study. The results from a recent study by Karaca Dinç et al (2021) suggest that both alexithymia and SPS may mediate this link.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, Patil and Silani (2014) have argued that, because alexithymic individuals show reduced concern for others, they are more likely to feel that “accidental” harms (i.e., those committed by someone who does not believe they are causing harm) are morally acceptable; in other words, their moral judgments are more lenient than those of individuals scoring low on alexithymia. Along similar lines, Zhang et al (2020) found that individuals scoring high in alexithymia were more likely to make utilitarian than deontological judgments (i.e., to conclude that “the ends justify the means”).…”
Section: Discussionmentioning
confidence: 82%
“…A recent study has shown that individuals with high alexithymia exhibit lower deontological inclinations than those with low alexithymia, whereas utilitarian inclinations do not vary between individuals with high alexithymia and those with low alexithymia. 31 Taken together, the current findings suggest that individuals with high alexithymia exhibit a greater preference for utilitarian judgments relative to those with low alexithymia, reflecting a reduced concern about causing harm (ie, weaker sensitivity to moral norms) rather than an increased concern about maximizing overall outcomes (ie, stronger sensitivity to consequences) and a general preference for inaction.…”
Section: Discussionsupporting
confidence: 53%
“…Brewer et al 27 found that moral acceptability judgments could be predicted by higher levels of alexithymia in a healthy population but not in a population with autism. Recently, Zhang et al 31 found that people with high levels of alexithymia make more utilitarian judgments than do those with low levels of alexithymia and that people with high levels of alexithymia exhibit reduced empathic concern, which diminishes deontological tendencies and, in turn, leads to more utilitarian judgments.…”
Section: Introductionmentioning
confidence: 99%
“…The current research contributes to the existing literature on utilitarian moral values by exploring the role of utilitarianism–egalitarianism trade‐off in climate change mitigation. Prior social psychological research has primarily relied on trolley problems to probe individuals' utilitarian or non‐utilitarian ethical inclinations (e.g., Amit & Greene, 2012; Manfrinati et al., 2013; Zhang et al., 2020). However, because of the highly complex and unrealistic nature of such scenarios, researchers have recently questioned their capability to accurately reflect people's genuine moral values and predict behavioural preferences in real‐world social dilemmas (Bauman et al., 2014; Dahl & Oftedal, 2019; Robinson, 2012).…”
Section: Discussionmentioning
confidence: 99%